Angiographic documented coronary arterial spasm in absence of critical coronary artery stenoses in a patient with variant angina episodes during exercise and dobutamine stress echocardiography. Issue 4 (1st April 2000) - Roffi, M; Meier, B; Allemann, Y
Abstract : Dobutamine stress echocardiography is widely performed as a useful diagnostic tool in patients with known or suspected coronary artery disease. Dobutamine induced myocardial ischaemia is frequently associated with ST segment depression. ST segment elevation is uncommon and is almost always associated with prior myocardial infarction or transient total coronary occlusion. Dobutamine induced ST segment elevation in absence of significant coronary artery disease is a rare condition and is supposed to be a consequence of severe coronary artery spasm. The case of a 58 year old man with variant angina episodes at rest, during exercise test, and dobutamine stress echocardiography is reported, in whom coronary spasm without significant coronary artery stenoses was documented angiographically.